OPTIMALISASI PELABUHAN TANJUNG PRIOK MENUJU PELABUHAN BERKELAS DUNIA - Yusuf Romadhon (Jurnal Logistik Indonesia, 2018)
This paper wants to find out the optimization of the performance of Tanjung Priok port towards a world-class port. Based on 4 port performance indicators (financial, operational, human resources and customers), it can be concluded that the port of Tanjung Priok must continue to improve in order to become a world class port. This is not easy because it must have the support of various existing stakeholders, not only PT Pelindo 2 as a port operator, but all parties related to it such as the Indonesian Government, sub-subsidiary PT Pelindo 2, also PT Pelindo employees.